XML descriptor based approach for real time data messaging - Poon, P.; Dillon, Tharam S.; Chang, Elizabeth; Feng, L. (IEEE Computer Society Press, 2006)
This paper presents an overview of the Real Time Markup Language (RTML). RTML is an XML profile which provides the syntactic representation for describing the semantics of real time data for exchange over distributed networked real time systems. For the basis of interoperability, this profile is described in the XML Schema language. This paper describes the background of this work and shows how the vocabularies are developed, and how it derives the extensibility of XML Schema in aiding the definition of data in real time systems in order to achieve the goal of interoperability.